2021
DOI: 10.21037/tau-21-384
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of asymptomatic renal artery pseudoaneurysm after robot-assisted partial nephrectomy

Abstract: Background: We assessed the natural history of renal artery pseudoaneurysm (RAP) after robot-assisted partial nephrectomy (RAPN).Methods: From May 2016 to September 2020, 106 patients underwent RAPN for renal tumors at our institution. Among 100 patients, excluding 6 who were ineligible for contrast-enhanced computed tomography (CE-CT), 4 underwent renal artery selective embolization (RAE), of which 2 cases were emergency RAE within 7 days after RAPN and the other 2 were prophylactic RAE 8 or more days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Partial nephrectomy has become superior to total nephrectomy in terms of the preservation of renal function and oncological outcomes, and the widespread use of robotic surgery has further accelerated this trend ( 4 - 7 ). Robot-assisted partial nephrectomy (RAPN) is performed at several centers in Japan ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial nephrectomy has become superior to total nephrectomy in terms of the preservation of renal function and oncological outcomes, and the widespread use of robotic surgery has further accelerated this trend ( 4 - 7 ). Robot-assisted partial nephrectomy (RAPN) is performed at several centers in Japan ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…RAP following RAPN is typically reported in the range of 1–5%. Factors such as the retroperitoneal approach, tumors located deeply within the renal parenchyma, larger tumor size, more complex tumor anatomy, renal sinus exposure, and young age (under 56 years) can affect its development ( 7 , 9 ). A review study reported that RAP after partial nephrectomy occurred at a mean of 14.9 days; however, since it could appear within 1–90 days, care should be taken for up to approximately 3 months after surgery ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation